Approximate Solution for advection dispersion equation of time Fractional order by using the Chebyshev wavelets-Galerkin Method - AL-Safi , Mohammed G. S.; Hummady, Liqaa Z. (Iraqi Journal of Science, 2021)
The aim of this paper is adopted to give an approximate solution for advection dispersion equation of time fractional order derivative by using the Chebyshev wavelets-Galerkin Method . The Chebyshev wavelet and Galerkin method properties are presented. This technique is used to convert the problem into the solution of linear algebraic equations. The fractional derivatives are described based on the Caputo sense. Illustrative examples are included to demonstrate the validity and applicability of the proposed technique.